Western Blot Assay for Quantitative and Qualitative Antigen Detection in Vaccine Development. Issue 1 (1st May 2014) - Kumar, Sanjai; Zheng, Hong; Mahajan, Babita; Kozakai, Yukiko; Morin, Merribeth; Locke, Emily
Abstract: Immunological methods for quantitative measurement, antigenic characterization, and monitoring the stability of active immunogenic component(s) are a critical need in the vaccine development process. This unit describes an enhanced chemiluminescence‐based western blot for quantitative detection of Plasmodium falciparum circumsporozoite protein (PfCSP), a major malaria candidate vaccine antigen. The most salient features of this assay are its high sensitivity and reproducibility; it can reliably detect ∼5 to 10 pg PfCSP expressed on native parasites or recombinantly expressed in Escherichia coli . Although described for a specific vaccine antigen, this assay should be applicable for any antigen‐antibody combination for which relevant detection reagents are available. Detailed stepwise experimental procedures and methods for data acquisition and analysis are described. Curr. Protoc. Microbiol . 33:18.4.1‐18.4.11. © 2014 by John Wiley & Sons, Inc.